Moss-produced human complement factor H with modified glycans has an extended half-life and improved biological activity - Tschongov, Todor; Konwar, Swagata; Busch, Andreas; Sievert, Christian; Hartmann, Andrea; Noris, Marina; Gastoldi, Sara; Aiello, Sistiana; Schaaf, Andreas; Panse, Jens; Zipfel, Peter F.; Dabrowska-Schlepp, Paulina; et al. (Frontiers in Immunology, 2024)
Most drugs that target the complement system are designed to inhibit the complement pathway at either the proximal or terminal levels. The use of a natural complement regulator such as factor H (FH) could provide a superior treatment option by restoring the balance of an overactive complement system while preserving its normal physiological functions. Until now, the systemic treatment of complementassociated disorders with FH has been deemed unfeasible, primarily due to high production costs, risks related to FH purified from donors' blood, and the challenging expression of recombinant FH in different host systems. We recently demonstrated that a moss-based expression system can produce high yields of properly folded, fully functional, recombinant FH. However, the half-life of the initial variant (CPV-101) was relatively short. Here we show that the same polypeptide with modified glycosylation (CPV-104) achieves a pharmacokinetic profile comparable to that of native FH derived from human serum. The treatment of FH-deficient mice with CPV-104 significantly improved important efficacy parameters such as the normalization of serum C3 levels and the rapid degradation of C3 deposits in the kidney compared to treatment with CPV-101. Furthermore, CPV-104 showed comparable functionality to serum-derived FH in vitro, as well as similar performance in ex vivo assays involving samples from patients with atypical hemolytic uremic syndrome, C3 glomerulopathy and paroxysomal nocturnal hematuria. CPV-104the human FH analog expressed in mosswill therefore allow the treatment of complement-associated human diseases by rebalancing instead of inhibiting the complement cascade.